Comparative Replication and Immune Activation Profiles of SARS-CoV-2 and SARS-CoV in Human Lungs: An Ex Vivo Study With Implications for the Pathogenesis of COVID-19. (9th April 2020) - Chu, Hin; Chan, Jasper Fuk-Woo; Wang, Yixin; Yuen, Terrence Tsz-Tai; Chai, Yue; Hou, Yuxin; Shuai, Huiping; Yang, Dong; Hu, Bingjie; Huang, Xiner; Zhang, Xi; Cai, Jian-Piao; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emerging coronavirus that has resulted in more than 2 000 000 laboratory-confirmed cases including over 145 000 deaths. Although SARS-CoV-2 and SARS-CoV share a number of common clinical manifestations, SARS-CoV-2 appears to be highly efficient in person-to-person transmission and frequently causes asymptomatic or presymptomatic infections. However, the underlying mechanisms that confer these viral characteristics of high transmissibility and asymptomatic infection remain incompletely understood. Methods: We comprehensively investigated the replication, cell tropism, and immune activation profile of SARS-CoV-2 infection in human lung tissues with SARS-CoV included as a comparison. Results: SARS-CoV-2 infected and replicated in human lung tissues more efficiently than SARS-CoV. Within the 48-hour interval, SARS-CoV-2 generated 3.20-fold more infectious virus particles than did SARS-CoV from the infected lung tissues ( P < .024). SARS-CoV-2 and SARS-CoV were similar in cell tropism, with both targeting types I and II pneumocytes and alveolar macrophages. Importantly, despite the more efficient virus replication, SARS-CoV-2 did not significantly induce types I, II, or III interferons in the infected human lung tissues. In addition, while SARS-CoV infection upregulated the expression of 11 out of 13 (84.62%) representative proinflammatory cytokines/chemokines, SARS-CoV-2 infection only upregulated 5 of these 13 (38.46%) key inflammatory mediators despite replicating more efficiently. Conclusions: Our study provides the first quantitative data on the comparative replication capacity and immune activation profile of SARS-CoV-2 and SARS-CoV infection in human lung tissues. Our results provide important insights into the pathogenesis, high transmissibility, and asymptomatic infection of SARS-CoV-2. Abstract : The comparative viral kinetics, cell tropism, and innate immune response profiles of SARS-CoV-2 and SARS-CoV in human lungs were characterized in ex vivo organ cultures. SARS-CoV-2 exhibited more efficient replication but induced significantly less host interferon and proinflammatory response than SARS-CoV.